Design and Development of the Space Shooters Game Using Pygame - Jazuli, Muhammad Syauqi; Rizki, Muhammad (Gameology and Multimedia Expert, 2024)
Space Shooter is a game that aims to shoot all the asteroids emerging from space while keeping the spaceship from colliding with them by maneuvering the spaceship. The main objective of this game is to accumulate as many points as possible by accurately shooting the asteroids. This game is developed using Pygame, a cross-platform Python module library designed for writing video games. Pygame includes computer graphics and sound libraries designed for use with the Python programming language. This study explores the development process of the "Space Shooter" game using Pygame and analyzes the effectiveness and reliability of this module in creating an interactive and engaging game. The results indicate that Pygame is an effective tool for game development, allowing easy integration of graphics and sound, and providing an intuitive interface for both novice and experienced developers.